Gita Savitri's YouTube on Content Childfree of Infertile People: A Reception Analysis (Serba Salah Di Mata Warganet) - Sihombing, Nathasya Aryanti Asyfaa; Esfandari, Diah Agung (eProceedings of Management, 2024)
This research is motivated by the controversial content presented by Gita Savitri on the YouTube page regardingchildfree choices. The purpose of this study is to analyze the reception responses of infertile people regarding GitaSavitri's content regarding childfree choices. The data analysis used in this research is Miles and Huberman'sinteractive data analysis. In this study, researchers used a qualitative method with a case study design. Data collectionwas carried out using a semi-structured interview approach to eight informants and studies in this study usingtechnique triangulation. The theory used as the theoretical basis in this research is the reception theory coined byStuart Hall. Stuart Hall's reception analysis explains the existence of three encodings in receiving a message includingdominant hegemonic, negotiated, and opposition. The results of this study found two things, first, Gita Savitri's contentabout Childfree was accepted. This acceptance occurs because it is based on background and additional insight.Second, the negotiated position, the relevant informant can accept cultural differences. This research brings up newfindings with the absence of opposition coding. Keywords-childfree, Gita Savitri, infertile, reception analysis, social media